The impact of coaches' character on youth basketball players - Hill, N. (University of Arkansas, 2018)
If utilized effectively, recreation and sports can serve as major tools for developing youth, improving the educational environment, and increasing the number of productive adults that are healthier physically and mentally to positively impact society. Most research targeting recreation and sports developing youth has the perspective primarily of parents and youth. Evaluating the character strengths of coaches and youth athletes who actively participate in team basketball is vital. An exploration of the value of basketball and character strengths of (n = 64) youth athletes, between the ages of 12 to 16 years, and the impact of their involvement with coaches that exhibit high and low character levels, drives this study. Surveys were sent electronically to 20 coaches and 13 completed the survey to determine their character strengths. The instrument consisted of a 96-item survey and 5pt Likert scale. Based on interview responses, character survey results, and voluntary consent of the coaches, nine coaches and ten teams (5 boys and 5 girls) were identified as participants for the study. Values In Action (VIA) Institute designed the adult and youth surveys. Tabulation of the coaches` survey results revealed the highest and lowest character strength levels. Triangulation of sources were used to acquire diverse information. Observations of teams and interviewing of coaches provided additional data. At the end of the basketball season, athlete participants from the ten teams completed a 96-item youth survey of character strengths. To disaggregate survey data, an independent t-test was conducted. The coach interview responses were transcribed verbatim using Revo software and subjected to a categorical aggregation analysis procedure. Thematic analysis and open coding were used to determine seven themes and 10 to 21 codes from interviews. All coaches indicated discipline and respect were high priorities and had four common character strengths: love of learning, leadership, fairness, and teamwork. The ttest revealed no significant (.145) impact of individual character strengths of youth athletes based on the coach character level. The study also recognizes that other factors outside of the sport of basketball, such as community-based organizations and faith-based organizations, may help increase youth character strengths and positive youth development.